2017
DOI: 10.1021/jacs.6b11467
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Ligand Selectivity from Absolute Binding Free Energy Calculations

Abstract: Binding selectivity is a requirement for the development of a safe drug, and it is a critical property for chemical probes used in preclinical target validation. Engineering selectivity adds considerable complexity to the rational design of new drugs, as it involves the optimization of multiple binding affinities. Computationally, the prediction of binding selectivity is a challenge, and generally applicable methodologies are still not available to the computational and medicinal chemistry communities. Absolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
196
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(206 citation statements)
references
References 94 publications
(197 reference statements)
7
196
1
2
Order By: Relevance
“…The degree inaccuracy of these predictions largely determines how effective they can be in prioritizing synthesis of small molecule ligands [105]. Retrospective estimates have suggested that current methodologies are capable of achieving about 1–2 kcal/mol inaccuracy for well-behaved protein-ligand systems [6, 122], but more work remains to be done to extend the applicability domain of these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The degree inaccuracy of these predictions largely determines how effective they can be in prioritizing synthesis of small molecule ligands [105]. Retrospective estimates have suggested that current methodologies are capable of achieving about 1–2 kcal/mol inaccuracy for well-behaved protein-ligand systems [6, 122], but more work remains to be done to extend the applicability domain of these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, statistical mechanics based absolute binding free energy methods such as DDM 4244 have increasingly been applied to compute protein-small molecule binding free energy 4550 , and we and others have shown that such methods can generate more accurate results compared with the more rapid docking and MM-PB(GB)/SA in estimating binding affinity for a number of protein-ligand systems 5153 . However, the DDM method has not yet been applied to small molecule-DNA (or RNA) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggestst hat Asp257 is more likely to be found in its monoprotonated state at pH 7. [45,46] For this study,t he solvation free energy (DG solv )o fDAPT was calculated in water and in aP OPC lipid bilayer to corroborate the highera ffinity of the ligand for the membrane environment observed during our US simulations. [45,46] For this study,t he solvation free energy (DG solv )o fDAPT was calculated in water and in aP OPC lipid bilayer to corroborate the highera ffinity of the ligand for the membrane environment observed during our US simulations.…”
mentioning
confidence: 66%